Sustaining mental health amidst high-pressure job scenarios: a narrative review - Kumar, Mahendra; Saini, Arti; Jeet, Kiron (International Journal Of Community Medicine And Public Health, 2024)
Today’s fast-paced world presents with increased work-related demands and pressures. These pressures may overwhelm an individual’s coping ability. From recognizing the signs of stress to implementing proactive measures for self-care, we embark on a journey to promote resilience and a healthy equilibrium between professional aspirations and mental well-being. Maintaining mental health and well-being is essential to living a healthy life even in high-pressure professional contexts. Nursing is one of the most challenging and demanding professions and use their psychological and emotional resources in service of their patients as well as navigating through the ups and downs of their own lives. Workplace stress has the potential to adversely impact both the physical and mental well-being of individuals, leading to a decline in job productivity through heightened stress levels. This leaves the professionals depleted and drained. Through this article, the author tries to highlight major stressors related to nursing and some practical coping measures.